Cardiac characterization of 16 patients with large NF1 gene deletions. (28th December 2012) - Nguyen, R; Mir, TS; Kluwe, L; Jett, K; Kentsch, M; Mueller, G; Kehrer‐Sawatzki, H; Friedman, JM; Mautner, V‐F
Abstract : The aim of this study was to characterize cardiac features of patients with neurofibromatosis 1 (NF1) and large deletions of the NF1 gene region. The study participants were 16 patients with large NF1 deletions and 16 age‐ and sex‐matched NF1 patients without such deletions. All the patients were comprehensively characterized clinically and by echocardiography. Six of 16 NF1 deletion patients but none of 16 non‐deletion NF1 patients have major cardiac abnormalities (p = 0.041). Congenital heart defects (CHDs) include mitral insufficiency in two patients and ventricular septal defect, aortic stenosis, and aortic insufficiency in one patient each. Three deletion patients have hypertrophic cardiomyopathy. Two patients have intracardiac tumors. NF1 patients without large deletions have increased left ventricular (LV) diastolic posterior wall thickness (p < 0.001) and increased intraventricular diastolic septal thickness (p = 0.001) compared with a healthy reference population without NF1, suggestive of eccentric LV hypertrophy. CHDs and other cardiovascular anomalies are more frequent among patients with large NF1 deletion and may cause serious clinical complications. Eccentric LV hypertrophy may occur in NF1 patients without whole gene deletions, but the clinical significance of this finding is uncertain. All patients with clinical suspicion for NF1 should be referred to a cardiologist for evaluation and surveillance.